Controls on the nature of loess particles and the formation of loess deposits. (26th January 2019) - Smalley, Ian; Marković, Slobodan B.
Abstract: The story (history) of a single loess particle can be told from the formation of the planet to the making of bricks. The modal loess particle chosen for study is a 30 μm quartz particle. Many factors bear on its complex history, starting with the formation of quartz units in the original granitic crustal rocks. Quartz units appear in the old granites as the product of a eutectic-like reaction. This controls particle size and ensures that sand is much the same wherever (and whenever) it is encountered. The eutectic reaction controls sand size; the silt size is controlled by crystalline defects which are introduced into the quartz by the high-low displacive transformation which the quartz undergoes as the system cools. Thus all quartz silt is much the same, as is the case for sand. The quartz clastic particles are surprisingly bi-modal, a more even size distribution might have been expected. The silt particles are largely formed by glacial grinding, by continental and mountain glaciers. These silt particles are distributed across the landscape by the action of large rivers, and deposited on floodplains. A critical stage in the story is the aeolian transportation of the particles which then form an airfall deposit. The glacially provided silt particles are quite close in size to the optimum for aeolian pick-up (∼80 μm). At this stage, on wind-fall deposition, the characteristic metastability is introduced into the loess deposit. The chief post-depositional process is the development of collapsibility, which is largely due to the movement of clay minerals to the main particle contacts. This low clay content of most loess deposits makes loess an ideal material for brick production.